THE INFLUENCE OF MOTIVATION AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AT THE ENVIRONMENT AND FORESTRY SERVICE OF RIAU ISLANDS PROVINCE - Siregar, Haposan; Indrayani, Indrayani; Khaddafi, Muammar; Yanita, Yanita; Irawati, Henny (RADJA PUBLIKA, 2022)
This study aims to see the influence of motivation and leadership style on the performance of the Environment and Forestry Service of Riau Islands Province. The sample used was 35 respondents from 55 employees. The sampling technique used was census. The data analysis method used is multiple regression. Based on the results of the data analysis, the regression equation is Y = 36,192 + 0.132X1 + 0.602X2 + e. Based on the t test, motivation has no positive and insignificant effect on performance, with another explanation that each reduction per unit of the motivation variable (X1), the performance variable (Y) will decrease by 0.132 or the performance will decrease by 13.2%. Leadership style has a positive and significant effect on performance. This means that each addition per unit of the Leadership Style variable (X2), the performance variable (Y) will increase by 0.602 or the performance will increase by 60.2%. Based on the F test, motivation and leadership style together have an effect on performance. Based on the coefficient of determination, that 30.9% of employee performance is determined by the variable of motivation and leadership style collectively, while the remaining 69.1% is determined by other factors.